Cerebrovascular disease, associated risk factors and antithrombotic therapy in a population screening cohort: Insights from the Belgian Heart Rhythm Week programme. (February 2017) - Proietti, Marco; Mairesse, Georges H; Goethals, Peter; Scavee, Christophe; Vijgen, Johan; Blankoff, Ivan; Vandekerckhove, Yves; Lip, Gregory YH
Background: Cerebrovascular disease confers a major healthcare burden worldwide and is a major cause of death and disability. Several well-established risk factors, such as atrial fibrillation (AF), are associated with cerebrovascular disease and antithrombotic therapy reduces risk. Design: This study was a subgroup analysis from the Belgian Heart Rhythm Week, a nationwide AF awareness programme. Methods: We studied subjects screened between 2012 and 2014 with available data on clinical risk factors and antithrombotic treatment. Results: Of the 38, 034 subjects eligible for this analysis, 1513 (4.0%) reported a positive clinical history for cerebrovascular disease. Logistic regression analysis found that age, hypertension, diabetes mellitus, history of vascular disease, history of heart failure and history of AF (all p < 0.001) were independently associated with cerebrovascular disease. Among subjects with history of cerebrovascular disease and AF, 1.7% were taking oral anticoagulant drugs only, while both oral anticoagulant drugs and aspirin were used in 61.5% of subjects, aspirin in 4.3% of patients and no antithrombotic therapy in 32.5% of subjects. Among those subjects without AF, the corresponding figures were 0.8, 9.5, 2.0 and 87.6%, respectively. Conclusions: The prevalence of cerebrovascular disease in this contemporary population screening project was higher than that reported in the general population and was associated with the major known stroke risk factors. Sub-optimal antithrombotic therapy management was evident, with a low use of oral anticoagulant drugs among patients with AF and a low use of aspirin among subjects without AF.